THE EFFECT OF VCD AND PANTHOM LEARNING ON THE LEARNING ACHIEVEMENT IN EARLY BREASTFEEDING INITIATION CARE VIEWED FROM THE STUDENTS’ LEARNING INTEREST (at MIDWIFERY ACADEMY OF GIRI SATRIA HUSADA WONOGIRI) - Y. Wahyunti Kristiningtyas (STIKES DUTAGAMA KLATEN, 2012)
Background: Early Breastfeeding Initiation Care is a skill that must be mastered to support the improvement of the midwives’ skills in providing quality services to their clients. Many students of Midwifery Schools have not mastered the skill as expected due to their low learning interest. Currently, on one hand the practicum learning on Early Breastfeeding Initiation Care has merely relied on the use of Phantom learning media. On the other hand, visualization with the use of VCD learning media is a way that can be used to make some abstract thing become tangible or real and that can accommodate the slow students in learning. The objectives of the research are to analyze: (1) the difference of effect between the use of VCD learning media and that of Phantom learning media on the learning achievement in Early Breastfeeding Initiation Care; (2) the difference of effect between the students’ high learning interest and the students’ low learning interest on the learning achievement in Early Breastfeeding Initiation Care; and (3) the interaction of effect between the use of the learning media and the students’ learning interest on the learning achievement in Early Breastfeeding Initiation Care. Method: The research used a quasi experiment method with the post-test only control group design.The data of the research were analyzed by using a two-way analysis of variance (ANOVA). Result: The results of the research are as follows: (1) the use of learning media has a significant effect on the learning achievement in Early Breastfeeding Initiation Care as indicated by Fo = 11.526 with the value of p = 0.001 < 0.05; (2) the learning interest has a significant effect on the learning achievement in Early Breastfeeding Initiation Care as shown by Fo = 5.167 with the value of p = 0.027 < 0.05; and (3) there is a significant interaction of effect between the use of the learning media and the students’ learning interest on the learning achievement in Early Breastfeeding Initiation Care as pointed out by Fo = 9.391 with the value of p = 0.003 < 0.05. Conclusion: Based on the results of the research, a conclusion is drawn that the use of appropriate and varied learning media is more effective of raising the students’ learning interest and enabling them to conduct an independent learning, which is adjusted to their own learning ability and interest so as to improve their learning achievement.